Nile blue as reporter dye in salt aggregation based-colorimetric aptasensors for peptide, small molecule and metal ion detection - Chovelon, Benoît; Peyrin, Eric; Ragot, Mailys; Salem, Nassim; Nguyen, Truong Giang; Auvray, Benjamin; Henry, Mickael; Petrillo, Mel-Alexandre; Fiore, Emmanuelle; Bessy, Quentin; Faure, Patrice; Ravelet, Corinne (Analytica chimica acta, 2023)
Herein, we report a novel approach for the design of a colorimetric aptasensor, relying on a Dye Salt Aggregation-based Colorimetric Oligonucleotide assay (DYSACO assay). This method is based on the use of an intercalating agent, Nile Blue (NB), whose aggregation capacities (and thus modification of its absorption spectrum) are drastically amplified by adding salts to the working solution. The presence of an aptamer could protect NB from such aggregation process due to its intercalation into double-stranded DNA and/or interaction with nucleobases. In response to the addition of the specific ligand, the competition between NB and the target for binding to the aptamer occurs, resulting in an increase in the dye salt aggregation and then in the blue-to-blank color change of the solution. The proof-of-principle was demonstrated by employing the anti-l-tyrosinamide aptamer and the assay was successfully applied to the trace enantiomer detection, allowing the detection of an enantiomeric impurity down to approximately 2% in a non-racemic sample. Through a reversed mechanism based on the increased capture of NB by DNA upon analyte binding, the sensing platform was further demonstrated for the Hg(II) detection. Water samples of different origin were spiked with Hg(II) analyte at final range concentrations comprised between (0.5–15 μM). An excellent overall recovery of 122 ± 14%; 105 ± 14%; 99 ± 9%; was respectively obtained from river, tap and mineral water, suggesting that the sensor can be used under real sample conditions. The assay was also shown to work for sensing the ochratoxin A and d-arginine vasopressin compounds, revealing its simplicity and generalizability potentialities. [Display omitted] •A novel approach for a colorimetric aptasensor based on a dye-salt aggregation phenomenon.•The DNA-intercalating dye colorimetric assay can be successfully used for four various targets.•Our assay is rapid, ease of use, cost-efficient and especially promising due to its simple, naked eye application.